The Readiness to Cooperate Within the Triple Helix Model in Poland - Bednarzewska, Kinga Ewa (Annales Universitatis Mariae Curie-Skłodowska. Sectio H. Oeconomia, 2021)
Theoretical background: The present article focuses on the assessment of the readiness of representatives of science, business and local administration in Poland to establish mutual cooperation in the areas of leadership, management style, competences and technologies. Subject literature refers to the cooperation of these three spheres as the triple helix. The literature, however, still lacks an assessment of readiness to cooperate from the perspective of science, business and administration. This article belongs to the area of institutional economics. Purpose of the article: The main purpose of this article was to present the functioning of cooperation between representatives of science, business and administration in Lublin and Warsaw. The methodological purpose was to develop the proprietary methodology of readiness to function according to the Triple Helix Readiness concept as a tool for assessing the level of readiness of the scientific, business and administration environment for mutual cooperation in Polish cities. The empirical purpose was to evaluate Polish cities in terms of their preparation for cooperation, as well as to formulate recommendations for the science, business and administration environment focused on increasing the effectiveness of mutual cooperation. Research methods: Qualitative and quantitative research methods were selected. Among the qualitative methods, a diagnostic survey was used. The Computer-Assisted Self Interviewing (CASI) online survey technique was also used, which is in line with the quantitative methodology of market and opinion research. The tool used to conduct the research was an Internet questionnaire addressed to stakeholders. For the present article we adopted the assumption that the adaptation of the modified Net Readiness methodology will enable us to assess the level of readiness of the science, business and administration environments in Poland to establish mutual cooperation. The author modified the original Net Readiness methodology for the purposes of conducting the research. Main findings: The adopted research hypothesis: cooperation between science, business and administration is determined by various factors. Diversifiation of the level of cooperation depends on the management style, leadership, level of competence and technology advancement used. The results of our research indicate that the readiness to cooperate with external entities depends on many factors. From the perspective of enterprises, these include the level of advancement of information systems, modern tools supporting knowledge management, their research and development activities, registered and transferred patents, trademarks and training expenditure. On the other hand, universities pay attention to the possibility of commercializing their solutions and later marketing them. Still other factors determine the readiness to undertake such cooperation on the part of cities and towns. The main added value of this article is that it adds to the scientific output an assessment of the readiness of the scientific, business and administration communities to cooperate under the triple helix model and recommendations focusing on increasing the effectiveness of their mutual cooperation.